2016
DOI: 10.21511/ee.07(2).2016.9
|View full text |Cite
|
Sign up to set email alerts
|

Role of external environmental factors in the failure of small enterprises in Angola

Abstract: The high failure rate of new small enterprises in Angola calls to attention the fact that they are not equipped enough to meet the challenges of sustainable economic growth, equitable distribution of wealth and job creation. The worrying impact on the Angolan landscape, as a consequence, has had economists scrambling for solutions in recent years. Moving from on the assumption that the current business climate has been a contributing factor, this paper attempts to examine the role of external environmental fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
0
0
Order By: Relevance
“…These results are also supported by Almeida (2019), who found that e-commerce businesses in Angola still suffer due to limited institutional support. Similarly, other research supports that the lack of institutions that subsidise the IT or m-commerce infrastructure and training of personnel of the business and/or promote science, technology and innovation may cause barriers to the use of m-commerce by small and medium enterprises (Siwundla, 2013;Chang & Dasgupta, 2015;Justino & Tengeh, 2016;Jaramillo, 2019). Furthermore, more respondents agreed (71%) that the lack of financial support impedes adoption.…”
Section: External Variablesmentioning
confidence: 99%
“…These results are also supported by Almeida (2019), who found that e-commerce businesses in Angola still suffer due to limited institutional support. Similarly, other research supports that the lack of institutions that subsidise the IT or m-commerce infrastructure and training of personnel of the business and/or promote science, technology and innovation may cause barriers to the use of m-commerce by small and medium enterprises (Siwundla, 2013;Chang & Dasgupta, 2015;Justino & Tengeh, 2016;Jaramillo, 2019). Furthermore, more respondents agreed (71%) that the lack of financial support impedes adoption.…”
Section: External Variablesmentioning
confidence: 99%